Genome-Wide Association Study and Transcriptome Differential Expression Analysis of the Feather Rate in Shouguang Chickens - Liu, Xiayi; Wu, Zhou; Li, Junying; Bao, Haigang; Wu, Changxin (Frontiers in Genetics, 2020)
Th feather rate phenotype in chicks, including early-feathering and late-feathering phenotypes, are widely used as a sexing system in the poultry industry. The objective of this study was to obtain candidate genes associated with the feather rate in Shouguang chicken. In the present study, we collected 56 of blood samples and 12 of hair follicle samples of flight feathers from female Shouguang chickens. Then we identified chromosome region associated with the feather rate by genome-wide association analysis (GWAS). We also performed RNA sequencing and analyzed differentially expressed genes between the early-feathering and late-feathering phenotypes using HISAT2, StringTie and DESeq2. We identified out a genomic region of 10.0-13.0 Mb of chromosome Z, which is statistically associated with the feather rate of Shouguang chickens at one-day old. After RNA sequencing analysis, 342 differentially expressed known genes between the early-feathering and late-feathering phenotypes were screened out, which were involved in epithelial cell differentiation, intermediate filament organization, protein serine kinase activity and peptidyl-serine phosphorylation, retinoic acid binding and so on. The SPEF2 gene and PRLR gene were the only two overlapping genes between the results of GWAS and differential expression analysis, which implies that SPEF2 and PRLR are possible candidate genes for the formation of chicken feathering phenotype in the present study. Our findings help to elucidate the molecular mechanism of the feather rate in chicks.